An overview on how Pd on resistive-based nanomaterial gas sensors can enhance response toward hydrogen gas. (26th July 2019) - Mirzaei, Ali; Yousefi, Hamid Reza; Falsafi, Farhad; Bonyani, Maryam; Lee, Jae-Hyoung; Kim, Jae-Hun; Kim, Hyoun Woo; Kim, Sang Sub
Abstract: Hydrogen has captured a lot of attention in recent years because its abundance, cleanness and one of the most promising sources of green energy. However, hydrogen has an explosive nature. Accordingly, detection of hydrogen leaks is important from a safety point of view. In this review paper, we use numerous examples to explain how Pd-decoration on the surfaces of nanomaterials can lead to enhancements in response and selectivity toward hydrogen gas. First, we describe the importance of hydrogen detection, then the properties of Pd and PdHx are reviewed, and metallic Pd hydrogen gas sensors are discussed. Finally, we comprehensively review different semiconducting gas sensors decorated with Pd with more emphasis on the sensing mechanism. This review paper provides a simple yet informative background for researchers working in this hot field. Highlights: Promising effects of Pd on the response enhancement to hydrogen gas are discussed. Different sensing mechanisms related to the presence of Pd are discussed. Different materials in combination with Pd as hydrogen gas sensors are discussed.